2006
DOI: 10.1007/s10591-006-9002-2
|View full text |Cite
|
Sign up to set email alerts
|

A Compulsive Buying Case: A Qualitative Analysis by the Grounded Theory Method

Abstract: This study analyzed a case of compulsive buying based on the grounded theory method. The client was a 24 year-old female Korean student who showed compulsive buying and excessive credit card use. The family therapy was performed between March 2001 and May 2004 in Korea. This study used the software ''Atlas.ti,'' producing 121 open codings and seven axis categories which included the following: (1) communication issues with friends or family members, (2) sibling relationships, (3) mother's parenting, (4) interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…Finally, qualitative evaluation of family therapy provided an appropriate methodology to explore mechanisms of change during CBD treatment (Salkovskis, 1995). Park, Cho, and Seo (2006) evaluated family therapy via grounded theory, in which a clear description of the 15-session treatment is provided. Rigorous analysis was employed on session transcripts, including a validation process by client feedback and then by independent researchers.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, qualitative evaluation of family therapy provided an appropriate methodology to explore mechanisms of change during CBD treatment (Salkovskis, 1995). Park, Cho, and Seo (2006) evaluated family therapy via grounded theory, in which a clear description of the 15-session treatment is provided. Rigorous analysis was employed on session transcripts, including a validation process by client feedback and then by independent researchers.…”
Section: Resultsmentioning
confidence: 99%
“…Kompulsif alıcılar düşük öz güven, endişe ve negatif duygusal durumları ile karakterize edilir. (Christenson et al, 1992;Lee, Lenno, & Rudd, 2000;Natarajan & Goff, 1992;DeSarbo & Edwards, 1996;Elliott, 1994;Park, Cho, & Seo, 2006;Valence et al, 1988).…”
Section: Literatür İncelemesiunclassified
“…(IF2014=2.467) Note: Each co-author has granted permission for the given publication to be included in the current dissertation. Foreword Park, Cho, and Seo (2006) describe a case of a 24-year-old Korean girl who accumulated $17,000 worth of debts by the time her mother brought her to treatment. Upon clinical assessment, she reported that her mother had very high expectations towards her regarding school performance, and regularly physically abused her first-born daughter.…”
Section: Acknowledgementmentioning
confidence: 99%